An analytical study on the water penetration and diffusion into concrete under water pressure - Yoo, J.; Lee, H.; Ismail, Mohamed (Elsevier BV, 2011)
Because concrete is a type of porous material, water or air can permeate freely into the concrete and that decreases the durability of concrete. Therefore, it is possible to permeate some corrosion inhibitors from the surface of concrete to inside the concrete due to its porosity even the steel-frame location by applying water pressure. The objective of this study is to investigate the depth of the water penetration in concrete forced under pressure. For achieving this purpose, the experiments for the depth of penetration were executed through selecting related factors and levels, such as water pressure and water pressurizing time. The water flow in concrete was examined theoretically and experimentally. As a result, in the case of the low water pressure approximately at 0.15 MPa or less, it was found that the flow showed a Darcy seepage flow and the same flow as an ordinary sand stratum. However, in the case of the high water pressure, the flow was diffused as a seepage flow that is accompanied by an internal deformation of concrete. This study attempts to develop a method that penetrates corrosion inhibitors to the location of steel bars and investigate the penetration depth of corrosion inhibitors by verifying water penetration in concrete under applied pressure. © 2010 Elsevier Ltd. All rights reserved.